EKONOMI ISLAM DAN PERANANNYA DALAM MEMBENTUK MASYARAKAT MADANI - Agus Toni (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2018)
Islamic economics that exist in the midst of a pluralistic society becomes its own barometer in conducting transactions in accordance with the nature of monotheism and humanity. As the substantive representation of the existence of Islam on this earth, which is called giving benefits wherever the and whenever are alternating for nature and its inhabitants, the Islamic economy must be able to respond to the society's movement from economic practices. The condition of the conventional system which is always alternating as a cause of the domination of the concept imposed by the authority makers to the public gives the impression of a human like a lab rat object. As a result the term social-levelling emerged with a set of inherent consequences. Islamic economics arises from a set of Islamic laws (al-Quran and hadith) as a source of primary law and ijtihad ulama 'as a secondary tool to give legitimacy to the interests and rights of every individual, society and government to obtain them without giving great consequences or losses to others. Deconstruction of human behavior in doing life to be adapted to the substance of Islam in relation to doing life become special for the Prophet Muhammad and his companions and tabi'i, tabi'in and ulama in the past and present in the framework of the development of behavior or ethics that substantially have the value of worship in the presence of God and has a positive value in the eyes of humans to become culture of the community itself as what has been realized by the Prophet in the city of Medina as a country that has a high civilization. This condition by scholars is termed Madani society or tamaddun society.